Adaptation and validation of a questionnaire to measure academic burnout in medical university students - Correa-López, Lucy E. (2019)
Introduction: Evaluate the validity and reliability of an instrument adapted to Peru to measure pre-presenceof Burnout Syndrome in university students of the career of Human Medicine at the UniversityRicardo Palma, taking as a starting point the Burnout Inventory of Maslach - Student Survey (MBISS). Methods: Cross-sectional analytical study, with level of application research. Validity was evaluated byanalysis of factorial structure with the principal components method, Kaiser-Meyer Olkin tests and Varimax rotation were applied; the reliability by the Cronbach alpha value. Results: 223 students from the Faculty of Human Medicine of the Ricardo Palma University were included, from November to December 2016. The prevalence of academic Burnout found was 28.25% (63); The Kaiser-Meyer Olkin fitness test had a result of 0.813 and Barlett's sphericity test of 1007.5 (p <0.000). The cumulative variance explained by 3 factors was calculated to be 55.4%. The instrument obtained a Cronbach's Alpha coefficient = 0.794, with correlations between the items, Emotional Exhaustion (α =, 855), Cynicism (α = 0.623) and Academic Efficiency (α = 0.744). Conclusion: The adapted and validated instrument gathers the psychometric properties to be considered a useful and reliable instrument initially in human medicine students of the Ricardo Palma University, presenting an adequate factorial structure and internal consistency to determine the level of Burnout Syndrome Academic.   DOI 10.25176/RFMH.v19.n1.1794